2015
DOI: 10.5152/anatoljcardiol.2015.6424
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the association between stroke/transient ischemic attack and atrial electromechanical delay in patients with paroxysmal atrial fibrillation

Abstract: Objective:This study aimed to evaluate the association between the history of stroke/transient ischemic attack (TIA) and inter- and intra-atrial electromechanical delay (EMD) in patients with paroxysmal atrial fibrillation (PAF).Methods:Patients diagnosed with PAF were included in this retrospective study. Patients who had a history of stroke or TIA were defined as the symptomatic group, whereas those who did not have such a history were defined as the asymptomatic group. On the basis of the transthoracic echo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…or a recovered vestibular neuritis? Could the patient have had paroxysmal AF with a cerebellar embolus [121, 122]? How far to go?…”
Section: Video Head Impulse Testingmentioning
confidence: 99%
“…or a recovered vestibular neuritis? Could the patient have had paroxysmal AF with a cerebellar embolus [121, 122]? How far to go?…”
Section: Video Head Impulse Testingmentioning
confidence: 99%
“…No significant correlation was found between ESUS and EMD. In contrast, Bayar et al [10] demonstrated that longer EMD was associated with stroke/TIA in patients with paroxysmal AF. They suggested that longer EMD predicts atrial conduction heterogeneity which is associated with stroke; therefore, evaluation of EMD could be helpful in determining patients at high-risk of stroke/TIA in PAF patients.…”
Section: Discussionmentioning
confidence: 88%
“…A sequential combination of cardiac monitoring improves outcomes in patients with ischemic stroke and transient ischemic events, irrespective of the underlying anatomical defect. [ 14 ] Yet 24 to 48-h Holter monitoring is still the first-line monitoring strategy after stroke to rule out AF, during which APCs and SVRs are frequently detected even in the absence of paroxysmal AF. [ 15 ] Unlike AF, there is no consensus about the management when SVRs and APCs are detected, and the clinical approaches of neurologists and cardiologists differ due to the resultant uncertainty and ambiguity.…”
Section: Discussionmentioning
confidence: 99%